Sikap dan Tindakan dalam Penanganan Keputihan Patologis pada Mahasiswi Fakultas Kesehatan Masyarakat Universitas Nusa Cendana Kupang - Ni Ketut Widyastuti; Engelina Nabuasa; Enjelita M. Ndoen (Media Kesehatan Masyarakat, 2021)
Vaginal discharge is one of the reproductive health issues experienced by female university students. This research aimed to describe the attitudes and actions of preventing and overcoming pathological vaginal discharge on female students in the Faculty of Public Health, Nusa Cendana University, Kupang. This was qualitative research, with six female students as informants obtained by purposive sampling technique. The results showed that the informants' attitude included feelings of fear and not fear of vaginal discharge experienced, and positive responses to the importance of actions of preventing and overcoming vaginal discharge. Pathological vaginal discharge precaution was generally undertaken by maintaining the hygiene of reproductive organs, while the act of overcoming pathological vaginal discharge was by using traditional methods and seeking treatment at health facilities. Female college students should have more information about vaginal discharge to prevent and overcome effectively the issue.